Caribboecetes progreso, a new species of sand-dwelling amphipod (Amphipoda: Corophiidea: Ischyroceridae) from the Gulf of Mexico, with a key for the genus - Paz-Ríos, Carlos E.; Ardisson, Pedro-Luis (Zootaxa, 2013)
A new species of the genus Caribboecetes Just, 1983 is described and illustrated from specimens collected on sandy bot-toms of the northern Yucatan Peninsula, southeastern Gulf of Mexico. Caribboecetes progreso sp. nov. differs from the closely related species Caribboecetes barbadensis Just, 1983 and Caribboecetes jenikarpae Just, 1984 by the inflated tri-angular anterolateral flange on basis of gnathopod 2, and from Caribboecetes justi Ortiz & Lemaitre, 1997 by the setose anterolateral surface of coxal plate 7 and basis of pereopod 7. Ecological notes for the new species, a morphological com-parison, map of distribution and key for all members in the genus are also provided.